Dct Based Image Watermarking - et. al., R. Shri raam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Use of social networking in the internet has an exponential growth in recent years, storage of data content is easy, the ease gave birth to issues like, piracy, authenticity and copyright protection while handling digital media. The art of hiding secret information inside an image is technically referred to as image watermarking or steganography. Steganography solemnly serves the purpose of delivering secret information, while image watermarking is used to verify integrity and authenticity of the image. Steganography focuses on the secret data embedded into the image and image watermarking focusses on the image. The watermarking schemes with the help of spread spectrum and quantisation, suffers scaling attacks and Host Signal Interference. The embedding parameter employed here is fixed and so it gets difficult for robustness and imperceptibility into account for all the images which are watermarked with this technique. This paper solves these problems referred before, Discrete Cosine Transform (DCT) based watermarking which assures the Peak Signal to Noise Ratio (PSNR) and Mean Square Error (MSE) values. Discrete Cosine Transform (DCT) based watermark scheme reduces Host Signal Interference (HSI). Spatial domain watermarking suffers serious spatial distortion and loss. Quantisation type of embedding technique results in distortion during geometrical operations like compression, filtering. Introduction of threshold for error serves the purpose of analysis of watermarked image. Spread Spectrum Scheme with Adaptive Embedding Strategy (SSAES) promises low Host Signal Interference (HSI) but fails to yield required Peak Signal to Noise Ratio (PSNR). The proposed system overcomes the drawbacks of Host Signal Interference (HSI) and scaling attacks.